Method for improving breakdown voltage of 5-series permanent magnetic ferrite

By mixing the lanthanum-free cobalt 5-series strontium ferrite pre-sintered with the recovered waste and adding specific auxiliary materials for processing, the problems of low eddy current loss and breakdown voltage in high-frequency applications are solved, and breakdown is achieved Significant increase in voltage and high-frequency application performance of materials.

CN119462120AInactive Publication Date: 2025-02-18SINOSTEEL ANHUI TIANYUAN TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411625032.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lanthanum-free cobalt 5-series strontium ferrite materials have large eddy current losses inside the magnet during high-frequency applications, resulting in heat generation of magnetic tile, reducing the service life of the motor, and the breakdown voltage of the material is relatively high at high voltages. Low, unable to meet market demand.

Method used

By mixing the lanthanum-free cobalt 5-series strontium ferrite prefix or prefixed material with the recovered waste at a ratio of 50:50, and adding specific auxiliary materials such as CaCO3, Al2O3, H3BO3, La2O3, Co2O3, SiO2, SrCO3 and White carbon black is subjected to ball milling, pressurized magnet molding and sintering to produce permanent magnet ferrite.

Benefits of technology

Effectively increase the breakdown voltage of 5-series permanent magnet ferrite, reduce the internal current of ferrite at high voltage, promote the application of ferrite at high frequency, and the process is simple and easy to use, suitable for large-scale industrial production. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134511320000041
    Figure BDA0005134511320000041
  • Figure BDA0005134511320000071
    Figure BDA0005134511320000071
Patent Text Reader

Abstract

The invention discloses a method for improving breakdown voltage of a 5-series permanent magnetic ferrite, relates to the technical field of preparation of permanent magnetic ferrites, and aims to solve the problem that the breakdown voltage cannot meet production and use requirements. The preparation method comprises the following steps: taking a lanthanum-cobalt-free series 5 strontium ferrite pre-sintered material or a mixture of the pre-sintered material and a recycled waste as a raw material, adding auxiliary materials, mixing, putting into a ball milling tank, adding water, carrying out sufficient ball milling, discharging out of the tank, filtering water, magnetizing, pressurizing and forming in a press, putting a formed blank into a kiln, heating, sintering, grinding and drying to obtain the permanent magnetic ferrite, wherein the lanthanum-cobalt-free series 5 strontium ferrite pre-sintered material or the mixture of the pre-sintered material and the recycled waste is used as a raw material; the auxiliary material comprises 0.5% of calcium carbonate and aluminum oxide, 0.1% of boric acid and lanthanum oxide and 0.2% of cobalt sesquioxide, and further comprises at least one of silicon dioxide, strontium carbonate and white carbon black; the adjusted auxiliary material comprises one or more of white carbon black, aluminum oxide, silicon dioxide, strontium carbonate and lanthanum oxide; the method disclosed by the invention is simple, effectively improves the breakdown voltage of the 5-series ferrite, is easy to be put into large-scale production, and can quickly realize industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permanent ferrite preparation, in particular to a method for improving the breakdown voltage of 5-series permanent ferrite. Background Art

[0002] In recent years, with the rapid development of my country's automobile industry represented by new energy vehicles and the electronics industry represented by high-end mobile phone manufacturing, the downstream manufacturers have an increasing demand for permanent ferrites. In addition to clear requirements for the magnetic properties of materials, new requirements have also been put forward for other parameters such as electrical properties of materials. Existing permanent ferrite materials have large eddy current losses inside the magnets when used at high frequencies, causing heating of the magnetic tiles and reducing the service life of the motor.

[0003] Permanent ferrite materials have a limit voltage under high voltage. After exceeding this voltage value, the current in the permanent ferrite material will increase sharply (from 0.1mA to more than 10mA in an instant), which is called breakdown phenomenon. This limit value is the breakdown voltage of ferrite. Improving the breakdown voltage of materials is the key to permanent ferrite materials in high-frequency applications. However, at present, domestic research on improving the breakdown voltage of permanent ferrite is basically blank.

[0004] At present, the breakdown voltage of lanthanum-free cobalt-5 series strontium ferrite on the market is generally around 0.1kV. When the voltage reaches 1kV, the current inside the ferrite can even reach tens of milliamperes, which is far lower than the current market requirements. Therefore, a method to increase the breakdown voltage of 5 series permanent magnet ferrite is urgently needed to solve this problem. Summary of the invention

[0005] The object of the present invention is to provide a method for improving the breakdown voltage of 5-series permanent ferrite to solve the problems mentioned in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for improving the breakdown voltage of 5-series permanent magnet ferrite, characterized in that it includes the following specific contents: using lanthanum-cobalt-free 5-series strontium ferrite pre-sintered material, or pre-sintered material and recycled waste material in a ratio of 50:50 as raw materials, adding auxiliary materials and mixing, putting into a ball mill, adding water and ball milling fully, filtering water after taking out of the tank, magnetizing and pressurizing in a press, and then putting the formed blank into a kiln for heating and sintering, grinding and drying to obtain permanent magnet ferrite;

[0007] Among them, the recycled waste materials are grinding materials and / or defective products generated during the preparation of lanthanum-free cobalt 5 series strontium ferrite, and the auxiliary materials include CaCO3, Al2O3, H3BO3, La2O3 and Co2O3, and also include at least one of SiO2, SrCO3 and white carbon black; in the method, CaCO3 accounting for 0.5% of the mass of the raw materials, H3BO3 accounting for 0.1% of the mass of the raw materials, and Co2O3 accounting for 0.2% of the mass of the raw materials are fixedly used, and the adjusted auxiliary materials include one or more of white carbon black, Al2O3, SiO2, SrCO3, and La2O3.

[0008] Preferably, the adjusted auxiliary materials are calculated as a percentage of the raw material mass, white carbon black is 0-0.1%, aluminum oxide is 0.01-0.5%, silicon dioxide is 0-0.1%, strontium carbonate is 0-0.1%, and lanthanum oxide is 0.3-0.8%.

[0009] Preferably, the preparation process of the above-mentioned ferrite includes: using lanthanum-free cobalt 5 series strontium ferrite pre-sintered material, or pre-sintered material and recycled waste material uniformly mixed in a ratio of 50:50 as raw material, adding auxiliary materials, putting it into a ball mill for ball milling for 8 to 12 hours, discharging the material and filtering the water, pressing the slurry into a round cake blank in a press, and then putting it into a roller kiln for sintering, the sintering temperature is 1210±10°C, and after the sintering is completed, taking out the ferrite sintered product, grinding both sides smooth and then drying.

[0010] Preferably, in the above method, the raw material is only pre-burned material, no white carbon black is added to the auxiliary material, Al2O3 accounts for more than 0.05% of the raw material mass, SiO2 and SrCO3 are used, and the amount of La2O3 is more than three times that of Co2O3.

[0011] In the preferred embodiment above, the breakdown voltage of the permanent ferrite obtained is preferably 5 to 8 kV.

[0012] Preferably, in the above method, the raw materials are pre-burned materials and recycled waste materials mixed in a ratio of 50:50, SiO2, SrCO3 and white carbon black are used simultaneously as auxiliary materials, and SiO2 accounts for less than 0.05% of the raw material mass, SrCO3 accounts for more than 0.05% of the raw material mass, and the amount of La2O3 does not exceed twice that of Co2O3.

[0013] In the preferred embodiment above, the breakdown voltage of the permanent ferrite obtained is preferably 1.5 to 4.5 kV.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. The method for improving the breakdown voltage of 5 series permanent magnet ferrite effectively improves the breakdown voltage of 5 series ferrite, reduces the internal current of ferrite under high voltage, and promotes the application of ferrite under high frequency.

[0016] 2. The method for improving the breakdown voltage of 5 series permanent ferrite is simple and easy to implement. It only requires adjusting the auxiliary materials of ferrite, is easy to put into large-scale production, and can be quickly realized in industrial application. DETAILED DESCRIPTION

[0017] A method for improving the breakdown voltage of 5-series permanent ferrites includes the following specific contents: using lanthanum-cobalt-free 5-series strontium ferrite pre-sintered material, or pre-sintered material and recycled waste material uniformly mixed in a ratio of 50:50 as raw materials, adding auxiliary materials and mixing, putting into a ball milling jar, adding water and ball milling fully, for reference, the ball milling can be 8-12 hours, filtering water after taking out of the jar, magnetizing and pressurizing in a press, and then putting the formed blank into a kiln for heating and sintering, and the sintering can be selected in a roller kiln, the sintering temperature is preferably 1210±10°C, grinding (grinding both sides until smooth) and drying to obtain the permanent ferrite;

[0018] The recycled waste materials are grinding materials and / or defective products produced in the preparation process of lanthanum-free cobalt 5 series strontium ferrite, and the auxiliary materials include CaCO3, Al2O3, H3BO3, La2O3 and Co2O3, and also include at least one of SiO2, SrCO3 and white carbon black; in the method, CaCO3 accounting for 0.5% of the mass of the raw materials, H3BO3 accounting for 0.1% of the mass of the raw materials, and Co2O3 accounting for 0.2% of the mass of the raw materials are fixedly used, and the adjusted auxiliary materials include white carbon black, Al2O3, SiO2, SrCO 3. and La2O3, further preferably, the adjusted auxiliary materials are calculated as a percentage of the mass of the raw materials, the amount of white carbon black is 0-0.1%, the amount of aluminum oxide is 0.01-0.5%, the amount of silicon dioxide is 0-0.1%, the amount of strontium carbonate is 0-0.1%, and the amount of lanthanum oxide is 0.3-0.8%. Regardless of the raw materials, this ratio can obtain the effect of the breakdown voltage of the prepared 5 series permanent magnet ferrite reaching more than 1kV, which is significantly higher than the existing products, but it cannot be optimized.

[0019] In a preferred embodiment, in order to further improve the breakdown voltage of the obtained 5 series permanent magnet ferrite, in the above method, if the raw material is only a pre-burned material, after testing, the following is a better solution: no white carbon black is added to the auxiliary material, Al2O3 accounts for more than 0.05% of the raw material mass, SiO2 and SrCO3 are used, and the amount of La2O3 is more than three times that of Co2O3. Under this scheme, the breakdown voltage of the obtained permanent magnet ferrite is 5 to 8 kV, which is much higher than the existing 5 series permanent magnet ferrite.

[0020] Correspondingly, in another preferred embodiment, the raw materials are pre-burned materials and recycled waste materials mixed evenly in a ratio of 50:50. After experiments, a better solution is provided below: SiO2, SrCO3 and white carbon black are used simultaneously in the auxiliary materials, and SiO2 accounts for less than 0.05% of the raw material mass, SrCO3 accounts for more than 0.05% of the raw material mass, and the amount of La2O3 does not exceed twice that of Co2O3. Under this solution, the breakdown voltage of the permanent magnet ferrite obtained is 1.5 to 4.5 kV.

[0021] In order to further illustrate the above invention, several embodiments are provided below. It should be noted that the following embodiments are only a small number of examples for illustrative purposes and are far from being all embodiments of the present invention. Therefore, the protection scope of the present invention should not be limited to these embodiments alone.

[0022] The pre-burned material used in the following embodiments is a 5-series lanthanum-free cobalt pre-burned material produced by a pre-burned material enterprise in Liaoning, but it is not a limitation of this patent, and other 5-series pre-burned material raw materials should also be within the scope of protection of this patent. The recycled waste is the production waste recycled from the production process of lanthanum-free cobalt 5-series strontium ferrite of Sinosteel Tianyuan Tongli Magnetic Material Factory, which is used for the reproduction of permanent magnet ferrite; Table 1 below is the auxiliary material formula of the embodiments and comparative examples, and the unit is the mass percentage of the raw materials.

[0023] Table 1. Excipients formulations for examples and comparative examples

[0024]

[0025] Comparative Example 1

[0026] The pre-sintered material and the recycled waste are mixed evenly in a ratio of 50:50, and after adding the auxiliary materials in Table 1, they are placed in a ball mill for 10 hours, the material is discharged and filtered, and the slurry is pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product is taken out, and the two sides are ground smooth and dried to obtain a permanent magnet ferrite. After the ferrite is placed on a voltage withstand tester to detect the breakdown voltage, the magnetic properties are tested. The test results are shown in Table 2.

[0027] Comparative Example 2

[0028] Add auxiliary materials to the pre-sintered material according to Table 1, put it into a ball mill for 10 hours, filter the water out of the material, press the slurry into a round cake blank in a press, and then sinter it in a roller kiln at a sintering temperature of 1210℃. After sintering, take out the ferrite sintered product, grind both sides smooth and dry it to obtain permanent ferrite. Put the ferrite on the voltage withstand tester to test the breakdown voltage, and then test the magnetic properties. The test results are shown in Table 2.

[0029] Comparative Example 3

[0030] The pre-sintered material and the recycled waste are mixed evenly in a ratio of 50:50, and after adding the auxiliary materials in Table 1, they are placed in a ball mill for 10 hours, the material is discharged and filtered, and the slurry is pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product is taken out, and the two sides are ground smooth and dried to obtain a permanent magnet ferrite. After the ferrite is placed on a voltage withstand tester to detect the breakdown voltage, the magnetic properties are tested. The test results are shown in Table 2.

[0031] Comparative Example 4

[0032] Add auxiliary materials to the pre-sintered material according to Table 1, put it into a ball mill for 10 hours, filter the water out of the material, press the slurry into a round cake blank in a press, and then sinter it in a roller kiln at a sintering temperature of 1210℃. After sintering, take out the ferrite sintered product, grind both sides smooth and dry it to obtain permanent ferrite. Put the ferrite on the voltage withstand tester to test the breakdown voltage, and then test the magnetic properties. The test results are shown in Table 2.

[0033] Example 1

[0034] The pre-sintered material and the recycled waste are evenly mixed in a ratio of 50:50, and after adding the auxiliary materials in Table 1, they are placed in a ball mill for 10 hours, and then the material is discharged and filtered. The slurry is pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product is taken out, and the two sides are ground smooth and dried to obtain a permanent ferrite. The ferrite is placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties are tested. The test results are shown in Table 2.

[0035] Example 2

[0036] The pre-sintered material and the recycled waste are evenly mixed in a ratio of 50:50, and after adding the auxiliary materials in Table 1, they are placed in a ball mill for 10 hours, and then the material is discharged and filtered. The slurry is pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product is taken out, and the two sides are ground smooth and dried to obtain a permanent ferrite. The ferrite is placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties are tested. The test results are shown in Table 2.

[0037] Example 3

[0038] The pre-sintered material and the recycled waste are evenly mixed in a ratio of 50:50, and after adding the auxiliary materials in Table 1, they are placed in a ball mill for 10 hours, and then the material is discharged and filtered. The slurry is pressed into a round cake blank in a press, and then placed in a roller kiln for sintering at a sintering temperature of 1210°C. After sintering, the ferrite sintered product is taken out, and the two sides are ground smooth and dried to obtain a permanent ferrite. The ferrite is placed on a voltage withstand tester to detect the breakdown voltage, and then the magnetic properties are tested. The test results are shown in Table 2.

[0039] Example 4

[0040] Add auxiliary materials to the pre-sintered material according to Table 1, put it into a ball mill and mill it for 10 hours, then remove the material and filter the water, press the slurry into a round cake blank in a press, and then put it into a roller kiln for sintering at a sintering temperature of 1210℃. After sintering, take out the ferrite sintered product, grind both sides smooth and dry it to obtain permanent ferrite. Put the ferrite on the voltage withstand tester to test the breakdown voltage, and then test the magnetic properties. The test results are shown in Table 2.

[0041] Example 5

[0042] Add auxiliary materials to the pre-sintered material according to Table 1, put it into a ball mill for 10 hours, filter the water out of the material, press the slurry into a round cake blank in a press, and then sinter it in a roller kiln at a sintering temperature of 1210℃. After sintering, take out the ferrite sintered product, grind both sides smooth and dry it to obtain permanent ferrite. Put the ferrite on the voltage withstand tester to test the breakdown voltage, and then test the magnetic properties. The test results are shown in Table 2.

[0043] Table 2. Breakdown voltage and magnetic properties test results of examples and comparative examples

[0044]

[0045] Note: The breakdown voltage and current in Comparative Examples 3 and 4 are all measured values ​​just after breakdown, and they only reach about 0.1 kV before breakdown.

[0046] Comparative Examples 3 and 4 do not use the auxiliary materials and adjustment method of the present invention. In particular, Comparative Example 4 is a common product on the market, and the breakdown voltages of both are far lower than 1 kV, which cannot meet the requirements.

[0047] Comparative Examples 1 and 2 use the auxiliary materials of the present invention, and the breakdown voltage reaches more than 1 kV, which is acceptable. However, compared with Comparative Example 1, after adjusting the auxiliary materials, the breakdown voltage of Examples 1, 2, and 3 is increased from less than 1 kV to 4.12 kV, and the breakdown voltage of the ferrite of the mixed raw materials is greatly improved; and compared with Comparative Example 2, the breakdown voltage of the ferrite of Examples 4 and 5 is increased to 6.99 kV after adjusting the auxiliary materials. Comparing the electrical properties and magnetic properties of Examples 1 to 5, Example 5 not only has a breakdown voltage as high as 5.91 kV, but also has a magnetic property that reaches the 5-series ferrite performance index, and has the best comprehensive performance.

[0048] In summary, this method reduces the current of ferrite under high voltage by adjusting specific auxiliary materials. At the same time, the magnetic properties are guaranteed and the breakdown voltage of 5 series permanent ferrite is improved; and the method provided by the present invention has a simple process, and the process is consistent with large-scale production, which is convenient for large-scale industrial production and can generate good economic benefits.

[0049] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.

[0050] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for increasing the breakdown voltage of 5-series permanent ferrite, characterized in that: The specific contents include: using lanthanum-free cobalt 5 series strontium ferrite pre-sintered material, or pre-sintered material and recycled waste material in a ratio of 50:50 as raw materials, adding auxiliary materials and mixing, putting into a ball milling tank, adding water and ball milling fully, filtering water after taking out of the tank, magnetizing and pressing in a press, and then putting the formed blank into a kiln for heating and sintering, grinding and drying to obtain permanent magnet ferrite; Among them, the recycled waste materials are grinding materials and / or defective products generated during the preparation of lanthanum-free cobalt 5 series strontium ferrite, and the auxiliary materials include CaCO3, Al2O3, H3BO3, La2O3 and Co2O3, and also include at least one of SiO2, SrCO3 and white carbon black; in the method, CaCO3 accounting for 0.5% of the mass of the raw materials, H3BO3 accounting for 0.1% of the mass of the raw materials, and Co2O3 accounting for 0.2% of the mass of the raw materials are fixedly used, and the adjusted auxiliary materials include one or more of white carbon black, Al2O3, SiO2, SrCO3, and La2O3.

2. A method for improving the breakdown voltage of 5-series permanent ferrite according to claim 1, characterized in that: The adjusted auxiliary materials are calculated as a percentage of the raw material mass, and the amount of white carbon black is 0-0.1%, the amount of aluminum oxide is 0.01-0.5%, the amount of silicon dioxide is 0-0.1%, the amount of strontium carbonate is 0-0.1%, and the amount of lanthanum oxide is 0.3-0.8%.

3. A method for improving the breakdown voltage of 5-series permanent ferrite according to claim 1, characterized in that: The preparation process of ferrite includes: using lanthanum-free cobalt 5 series strontium ferrite pre-sintered material, or pre-sintered material and recycled waste material uniformly mixed in a ratio of 50:50 as raw material, adding auxiliary materials, putting it into a ball mill for ball milling for 8 to 12 hours, discharging the material and filtering the water, pressing the slurry into a round cake blank in a press, and then putting it into a roller kiln for sintering at a sintering temperature of 1210±10°C. After sintering, take out the ferrite sintered product, grind both sides to make it smooth, and then dry it.

4. A method for improving the breakdown voltage of 5-series permanent ferrite according to any one of claims 1 to 3, characterized in that: In the method, the raw material is only pre-burned material, no white carbon black is added to the auxiliary material, Al2O3 accounts for more than 0.05% of the raw material mass, SiO2 and SrCO3 are used selectively, and the amount of La2O3 is more than three times that of Co2O3.

5. A method for improving the breakdown voltage of 5-series permanent ferrite according to any one of claims 1 to 3, characterized in that: In the method, the raw materials are pre-burned materials and recycled waste materials uniformly mixed in a ratio of 50:50, SiO2, SrCO3 and white carbon black are used as auxiliary materials at the same time, and SiO2 accounts for less than 0.05% of the raw material mass, SrCO3 accounts for more than 0.05% of the raw material mass, and the amount of La2O3 does not exceed twice that of Co2O3.

6. A method for improving the breakdown voltage of 5-series permanent ferrite according to claim 4, characterized in that: The breakdown voltage of the permanent ferrite prepared by the method is 5-8 kV.

7. The method for improving the breakdown voltage of 5-series permanent ferrite according to claim 5, characterized in that: The breakdown voltage of the permanent ferrite prepared by the method is 1.5-4.5 kV.

Citation Information

Patent Citations

  • Characterization analysis method for migration of lanthanum and cobalt ions in lanthanum-cobalt substituted strontium ferrite permanent magnet material

    CN103408296A

  • High-voltage-resistant permanent magnetic ferrite magnet and manufacturing method thereof

    CN111470858A